Disputes on the termination of the right to land plots: a review of judicial practice - Nazaralieva, A.B.; Niyazova, A.N. (Bulletin of the Karaganda University “Law Series”, 2023)
The article is devoted to the study of the range of issues arising in the judicial practice on land disputes. Lawsuits arising from land legal relations occupy a significant place among ongoing proceedings in the courts of the Kyrgyz Republic. In this connection, it is important to analyze and systematize the existing practice in this area. Of particular interest are the problems arising from the seizure and redemption of land, including for state and public needs. The authors of this study made an attempt to study the proposed issues, give examples of judicial cases of interest, and also suggested possible ways to improve the norms of legislation in this area. In the framework of this study, both general scientific methods and special legal methods, such as formal legal and comparative legal methods, were used. Undoubtedly, the issues of termination of rights to land plots, including on the territory of the Kyrgyz Republic, are relevant from the point of view of theoretical research, while also having practical significance. Carrying out analysis and statistics of considered civil, economic and administrative cases, especially related to land legal issues, carried out on an ongoing basis, would contribute to the awareness and legal literacy of the parties for correct and legally verified appeal to the court.